SPATIAL DETERMINANTS OF ACCOMMODATION AND FOOD SERVICES SECTOR GRDP IN EAST JAVA: A GEOGRAPHICALLY WEIGHTED PANEL REGRESSION APPROACH - Rivo Firdauzy Febriansyah; Duwi Yunitasari; Siti Komariyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study investigates spatial heterogeneity in the determinants of Gross Regional Domestic Product (GRDP) in the accommodation and food services sector across 38 districts and cities in East Java Province, Indonesia, over the period 2022–2024. Using Geographically Weighted Panel Regression (GWPR), the analysis examines how tourist arrivals, accommodation capacity, per capita expenditure, and local government tourism budgets influence sectoral GRDP at the local level. The results reveal an extreme spatial concentration of tourism-based economic activity (Gini coefficient = 0.82), with Surabaya City contributing 66.36% of provincial sectoral GRDP. The GWPR model significantly outperforms the global panel regression, with R² increasing from 0.412 to 0.847, confirming the presence of strong spatial heterogeneity. Local coefficient estimates identify four regional typologies: high-efficiency regions, supply-driven regions, demand-driven regions, and low-efficiency regions. Tourist arrivals exhibit the highest elasticity in destination-oriented regions (reaching 0.94 in Banyuwangi), while accommodation capacity has the strongest effect in metropolitan cores (up to 1.23 in Surabaya). These findings indicate that spatially targeted policies aligned with local economic structures are substantially more effective than uniform provincial interventions. The study provides empirical support for place-based tourism development strategies within the Regional Tourism Master Plan (RIPPARDA) framework.